ALASAN PEMERINTAH RWANDA MENINGKATKAN TARIF IMPOR SECOND HAND CLOTHING (SHC) AMERIKA SERIKAT TAHUN 2016-2018 - Dwipayanthi, Dinda Ratna; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
This study aims to describe the reasons Rwanda’s decision to increase import tariff of United States Second Hand Clothing (SHC) in 2018. SHC provides low-cost clothing for people living in poverty. However, since 2016 Rwanda increased tariffs on imported SHC. SHC is one factor in the near-collapse of the garment industry in Rwanda. This research is analyzed using descriptive qualitative research methods with secondary data collection focusing on state level analysis. The theoretical framework in this research used the concept of determinant of foreign policy and economic interest. This research found that Rwanda’s decision to increase import tariff could protect the national economic industry in Rwanda. Key words: Second Hand Clothing, Determinant of Foreign Policy, Economic Interest, Infant Industry.